Pelatihan Pemanfaatan PowerPoint dan iSpring sebagai Media Pembelajaran Inovatif di SDN Pengengat, Kab. Lombok Tengah oleh Mahasiswa Kampus Mengajar 2 Tahun 2021 - M. Nazir Maulana; Tedi Dzulkipli; Melinia Putri; Amalia Devon; Heri Setiawan; Husnul Khotimah (Dedikasi Cendekia: Warta Pengabdian Pendidikan, 2025)
This community service activity aims to improve teachers' ability to utilize technology as an innovative learning medium through training in the use of PowerPoint and iSpring. The target of this activity is teachers at SDN Pengengat, Pujut District, Central Lombok Regency, who have so far predominantly used conventional methods in the teaching and learning process. The method of implementing the activity is carried out in a participatory manner and is based on direct practice, including basic introduction sessions, media creation practices, and ongoing mentoring. The results of the activity show a significant increase in teachers' understanding and skills in creating interactive teaching media. Teachers are able to integrate various multimedia features, such as animation, audio, video, and interactive quizzes into learning materials. In addition to improving technical skills, there is also a positive change in attitude towards the use of technology in learning. Although there are still obstacles such as limited devices and networks, this activity proves that appropriate training can encourage learning innovation at the elementary school level. This activity is a form of real contribution from Kampus Mengajar students in supporting sustainable educational transformation in the region.